Autoimmune and immunoserological markers of COVID-19 pneumonia: Can they help in the assessment of disease severity - Stjepanovic, Mihailo I.; Stojanovic, Maja R.; Stankovic, Sanja; Cvejic, Jelena; Dimic-Janjic, Sanja; Popevic, Spasoje; Buha, Ivana; Belic, Slobodan; Djurdjevic, Natasa; Stjepanovic, Mirjana M.; Jovanovic, Dragana; Stojkovic-Laloševic, Milica; et al. (Frontiers in Medicine, 2022)
Background: Immune dysregulation and associated inefficient anti-viral immunity during Coronavirus Disease 2019 (COVID-19) can cause tissue and organ damage which shares many similarities with pathogenetic processes in systemic autoimmune diseases. In this study, we investigate wide range autoimmune and immunoserological markers in hospitalized patients with COVID-19. Methods: Study included 51 patients with confirmed Severe Acute Respiratory Syndrome Coronavirus 2 infection and hospitalized due to COVID-19 pneumonia. Wide spectrum autoantibodies associated with different autoimmune inflammatory rheumatic diseases were analyzed and correlated with clinical and laboratory features and pneumonia severity. Results: Antinuclear antibodies (ANA) positivity was found in 19.6%, anti-cardiolipin IgG antibodies (aCL IgG) in 15.7%, and anti-cardiolipin IgM antibodies (aCL IgM) in 7.8% of patients. Positive atypical x anti-neutrophil cytoplasmic antibodies (xANCA) were detected in 10.0% (all negative for Proteinase 3 and Myeloperoxidase) and rheumatoid factor was found in 8.2% of patients. None of tested autoantibodies were associated with disease or pneumonia severity, except for aCL IgG being significantly associated with higher pneumonia severity index (p=0.036). Patients with reduced total serum IgG were more likely to require non-invasive mechanical ventilation (NIMV) (p<0.0001). Serum concentrations of IgG (p=0.003) and IgA (p=0.032) were significantly lower in this group of patients. Higher total serum immunoglobulin A ( IgA) (p=0.009) was associated with mortality found in patients with unfavorable outcome, with no difference in serum IgG (p=0.115) or IgM (p=0.175). Lethal outcome was associated with lower complement C4 (p=0.013), while there was no difference in complement C3 concentration (p=0.135). Conclusion: Increased autoimmune responses are present in moderate and severe COVID-19. Severe pneumonia is associated with the presence of aCL IgG, suggesting their role in disease pathogenesis. Evaluation of serum immunoglobulins and complement concentration could help assess the risk of non invasive mechanical ventilation NIMV and poor outcome.